Tax Dispute in a Digital Economy: The Legal Implication in Nigeria - Ahmodu, Abdul-Lateef Olamide; Ezeani, N. S. (NIU Journal of Social Sciences, 2023)
The study examines the tax disputes in a digital economy with a precise focused on the legal implications in Nigeria. The study explored some of the tax jurisdiction law in the digital economy. This digital economy encompasses various revenue streams and business models, such as e-commerce, digital services, online advertising, and software licensing. The study also identify transfer pricing issues arising from tax authorities in questioning the pricing of intra-group transactions involving intangible assets such as intellectual property rights or digital content. The significance of Permanent Establishment (PE) in determining a business's tax liabilities in a foreign jurisdiction were also discussed. The disputes that are commonly arise when taxpayers fail to fulfill their reporting obligations and the legal implications. However, the study highlighted the development of tax laws and regulations, leading to divergent views between taxpayers and tax authorities on the application and interpretation of tax laws in the digital context. Thus, the study employed a phenomenological research method, specifically a systematic review approach to examine the pertinent literature. Based on this study, it was concluded that tax authorities in Nigeria need to possess a deep understanding of the legal ramifications associated with tax disputes in the digital economy. To successfully navigate such disputes and contribute to an acquiescent and transparent digital economy, the study recommends that Nigerian tax collectors should closely collaborate with legal professionals, continuously update their knowledge of tax regulations, use technology solutions, and offer proactive advice to their clients. They should effectively handle tax disputes and play a vital role in ensuring a transparent and amenable digital economy. Keyword: Tax Disputes, Digital Economy, Legal Implication and Accountants